Pengenalan dan Edukasi Senam Jantung Sehat Di Poli Jantung Pada Era Pandemi Covid-19 di Rumah Sakit Akademik Universitas Mataram - Anak Agung Sagung Mas Meiswaryasti P; Catarina Budyono; Ima Arum Lestarini; Novia Andansari Putri; Niti Wedayani; Sekar Partiwi (Universitas Mataram, 2022)
Heart disease is included in the list of diseases that cause the most deaths in Indonesia. Starting from a heart attack, coronary heart disease, heart failure to cardiac arrest. All these diseases are closely related to the application of an unhealthy lifestyle, one of which is lazy to move. Healthy heart exercise is the most popular choice of exercise in the community. This exercise is composed of various movements that benefit the heart. Starting from strengthening the heart muscle, preventing damage to the arteries due to high cholesterol, lowering high blood pressure, and keeping weight under control. Health workers play an important role in providing education related to the health of the people of West Nusa Tenggara. Lack of public knowledge about one way to prevent coronary heart disease is the responsibility of health workers to provide education. Because the lack of knowledge to prevent it causes an increase in morbidity and mortality caused by heart disease. The approach steps taken in this program are counseling or providing education to visitors to the Cardiology Polyclinic at the Mataram University Hospital. Community service was carried out at the Poly Hospital of UNRAM and also in the hall of the UNRAM Hospital. Attended by 30 participants and 1 speaker as well as 4 young doctors and 1 lab employee from the Faculty of Medicine, University of Mataram. From the analysis of the questionnaire distributed, 28 people scored less than 50 in answering questions about risk factors and the dangers of obesity and there was a change in the score to 26 respondents who got a score of 80 after being given education. This shows that after the education is given, public knowledge about cardiac gymnastics increases.